Peran Ruang Komunal terhadap Keterikatan Fungsional (Functional Attachment) di Panti Wreda Pengayoman Semarang - Muhammad Nico Arinda; Gagoek Hardiman (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2024)
This research discusses the function of "communal space" in the environment of nursing homes in relation to functional attachment for the elderly. Functional attachment can occur because their needs are met in a certain place. This research aims to analyze the role of communal spaces in enhancing functional attachment among the elderly at Panti Wreda Pengayoman Semarang. This research uses a qualitative approach. Data collection in this research was conducted through interviews and observations at Panti Wreda Pengayoman Semarang. This research uses purposive sampling technique. The research results show that the availability of communal spaces, clear functions and activities of spaces, accessibility and connectivity between spaces, the availability of green areas, and behavior towards the environment play an important role in functional improvement to achieve attachment to a specific place.